ダイ 2 ジ ナンキョク チイキ カンソクタイ ジュウリョク ブモン ホウコク - 原田, 美道; ハラダ, ヨシミチ; 鈴木, 弘道; スズキ, ヒロミチ; 大橋, 伸一; オオハシ, シンイチ; HARADA, Yoshimichi; SUZUKI, Hiromiti; OHASHI, Shin-ichi (国立極地研究所, 1959)
P(論文) departmental bulletin paper